Estudio de Factibilidad para implementar una Ferretería de materiales de construcción en la parroquia Selva Alegre del cantón Saraguro Provincia de Loja - Ochoa Moreno, Lili Yadira (2024)
The general objective of the feasibility study entitled “Feasibility Study to implement a hardware store of construction materials at Selva Alegre, parish of Saraguro canton, Loja Province” is to determine the viability in the economic, technical, financial and profitability aspects for the creation of a hardware store that offers construction materials in the Selva Alegre parish. The study arises from the need to satisfy the needs of the community in the commercialization of materials for construction, industry and home, with the best quality, guarantee and at the lowest price, through excellence in customer service. The methodology used for the research is quantitative, with an exploratory and descriptive deductive method with a non-experimental design and the use of surveys as a research technique. The target population is 220 families, representing approximately 47.8% of the total family population, which corresponds to 460 families. The surveys collected made it possible to determine market acceptance, unsatisfied demand, and potential, real and actual demand. In addition, the installed capacity, the location of the establishment, the necessary infrastructure and the technological components were analyzed. In financial terms, the total investment of the project is estimated at $117,027.87, with $77,027.87 contributed by the partners and $40,000.00 financed by a bank. The financial results indicate a Net Present Value (NPV) of $3993.04, a positive Internal Rate of Return (IRR) of 11.17%, a payback period of 7 years, 0 months and 2 days, and a Benefit-Cost Ratio of $1.35. In addition, the sensitivity analysis shows that the project can withstand increases in costs and decreases in revenues. Therefore, the project is viable and feasible.